Kairos study protocol: a multidisciplinary approach to the study of school timing and its effects on health, well-being and students’ performance - Gabaldón-Estevan, Daniel; Carmona-Talavera, Diego; Catalán-Gregori, Belén; Mañas-García, Elena; Martin-Carbonell, Vanessa; Monfort, Lucía; Martinez-Besteiro, Elvira; González-Carrasco, Mònica; Hernández-Jiménez, María Jesús; Täht, Kadri; Talavera, Marta; Ancheta-Arrabal, Ana; et al. (Frontiers in Public Health, 2024)
Recent evidence from chronobiology, chssronomedicine and chronopsychology shows that the organisation of social time (e.g., school schedules) generally does not respect biological time. This raises concerns about the impact of the constant mismatch between students’ social and internal body clocks on their health, well-being and academic performance. The present paper describes a protocol used to investigate the problem of (de) synchronisation of biological times (chronotypes) in childhood and youth in relation to school times. It studies the effects of student chronotype vs. school schedule matches/mismatches on health behaviours (e.g., how many hours students sleep, when they sleep, eat, do physical activity, spend time outdoors in daylight) and learning (verbal expression, spatial structuring, operations) and whether alert-fatigue levels mediate this effect alignments/misalignments on learning (verbal expression, spatial structuring, operations) and their mediation by alert-fatigue levels. The novelty of our protocol lies in its multidisciplinary and mixed methodology approach to a relevant and complex issue. It draws on up-to-date knowledge from the areas of biology, medicine, psychology, pedagogy and sociology. The methods employed include a varied repertoire of techniques from hormonal analysis (cortisol and melatonin), continuous activity and light monitoring, self-registration of food intake, sleep timings, exercise and exposure to screens, alongside with systematic application of cognitive performance tests (e.g., memory, reasoning, calculation, attention) and self-reported well-being. This comprehensive and interdisciplinary protocol should support evidence-based education policy measures related to school time organisation. Appropriate and healthier school timetables will contribute to social change, healthier students and with more efficient learning. The results of studies using a similar methodology in other countries would ensure replication and comparability of results and contribute to knowledge to support policy making.